Complete agile metrics and planning (video collection) - Norman, Tommy (Pearson, 2024)
This video collection shows how to measure Agile teams effectively and help create an environment that maximizes value and learning, while also leveraging the power of Agile estimating and planning to manage client and stakeholder expectations throughout every stage of software development.
Online resource; title from title details screen (O'Reilly, viewed August 5, 2024)
Keywords: Agile project management; Agile software development -- Management; Gestion de projet agile; Méthodes agiles (Développement de logiciels); Gestion; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet